2016
DOI: 10.3390/ijms17111951
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of mRNA and miRNA in Somatic Embryos of Larix leptolepis Subjected to Hydrogen Treatment

Abstract: Hydrogen is a therapeutic antioxidant that has been used extensively in clinical trials. It also acts as a bioactive molecule that can alleviate abiotic stress in plants. However, the biological effects of hydrogen in somatic embryos and the underlying molecular basis remain largely unknown. In this study, the morphological and physiological influence of exogenous H2 treatment during somatic embryogenesis was characterized in Larix leptolepis Gordon. The results showed that exposure to hydrogen increased the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 64 publications
(98 reference statements)
0
14
0
Order By: Relevance
“…This effect of the hydrogen treatment was linked to the expression of stress-related genes in larch PEMs, reduced reactive oxygen species (ROS) levels, and enhanced antioxidant enzyme activity. These findings indicated that increased rates of active PEMs and normal somatic embryos may be, at least partially, a result of reduced ROS levels after hydrogen treatment (Liu et al, 2016). Up-regulation of flavonoid biosynthesis genes and related transcription factors in the EMs of Norway spruce may have promoted embryo development by regulating polar auxin transport and the functions of housekeeping enzymes, in addition to the more general role of flavonoids in ROS scavenging and abiotic stress resistance (Reza et al, 2018).…”
Section: Plant Growth Regulators and Stress-regulated Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect of the hydrogen treatment was linked to the expression of stress-related genes in larch PEMs, reduced reactive oxygen species (ROS) levels, and enhanced antioxidant enzyme activity. These findings indicated that increased rates of active PEMs and normal somatic embryos may be, at least partially, a result of reduced ROS levels after hydrogen treatment (Liu et al, 2016). Up-regulation of flavonoid biosynthesis genes and related transcription factors in the EMs of Norway spruce may have promoted embryo development by regulating polar auxin transport and the functions of housekeeping enzymes, in addition to the more general role of flavonoids in ROS scavenging and abiotic stress resistance (Reza et al, 2018).…”
Section: Plant Growth Regulators and Stress-regulated Pathwaysmentioning
confidence: 99%
“…However, they still failed to develop into mature somatic embryos, indicating that additional factors or developmental pathways are involved in embryo maturation (Park et al, 2010). The ability to control oxidative stress to prevent oxidative damage and maintain cell and protein structure appeared to be a key component for embryogenesis induction in larch (Liu et al, 2016). Treatments with hydrogen, an antioxidant molecule, increased the proportion of active pro-embryogenic cells in PEMs, and induced normal somatic embryos.…”
Section: Plant Growth Regulators and Stress-regulated Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The genomic DNA of L. kaempferi was isolated from the embryonal-suspensor mass with the CTAB plant genome DNA rapid extraction kit (Aidlab, China) according to the manufacturer's protocols. MIR171 sequences were amplified from genomic DNA with Platinum® Taq DNA polymerase (Invitrogen, USA) with specific primers (Table S1), which were designed based on the annotation of miRNA (Liu et al 2016;Zhang et al 2012) of L. kaempferi. The PCR products were purified with the Gel Extraction kit (Tiangen, China), ligated into the pEASY®-T1 simple cloning vector (Transgen, China), and sequenced.…”
Section: Sequence Cloning and Analysis Of Mir171 Genesmentioning
confidence: 99%
“…miRNA profiling using NGS has revolutionised miRNA analysis and there are still new instruments, sequencing platforms, and new methods that appear, such as sRNA-seq using single-cell sequencing [ 81 ] which provide new opportunities for analyses also during embryogenesis. Until now, sRNA-seq analyses have been performed during embryogenesis in Picea sprus [ 82 ], P. pinaster [ 39 ], Picea glauca [ 30 ], Triticum aestivum [ 83 ], Arabidopsis [ 28 , 30 , 35 , 38 , 41 , 84 ], Dimocarpus longan [ 85 ], Zea mays [ 86 ], Citrus sinensis [ 87 ], Larix leptolepis [ 88 ], Gossypium hirsutum [ 89 , 90 ], Phyllostachys heterocycla [ 91 ], Oryza sativa [ 92 ], and Lilium pumilum [ 93 ] (for SE reviewed in [ 94 ]). Plant embryogenesis is challenging to analyse due to the small, early embryos that are deeply embedded in the maternal tissues, which often results in RNA contamination from maternal tissue, and due to difficult distinguishing of the cells that are undergoing SE within an explant tissue, protocols, which are specifically dedicated for ZE and SE, have been developed and successfully used for miRNA analysis [ 28 , 38 , 84 , 95 ].…”
Section: Available Plant Mirna-dedicated Research Toolsmentioning
confidence: 99%